2019
DOI: 10.1001/jamaoto.2018.4512
|View full text |Cite
|
Sign up to set email alerts
|

Association of Head and Neck Cancer With Mental Health Disorders in a Large Insurance Claims Database

Abstract: IMPORTANCE Although a few studies have shown that mental health disorders (MHDs) are strongly associated with the 5-year survival and recurrence rates in patients with head and neck cancer (HNC), none have been replicated in a large-scale study.OBJECTIVE To describe the prevalence of MHDs in patients with HNC and the potential associations with survival and recurrence using a large insurance claims database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Following HNC diagnosis, the prevalence increased to 29.9%. 20 A separate study highlighted that the prevalence of a functional genetic polymorphism of the serotonin transporter gene was not significantly different between control depression patients and HNC depression patients who had completed treatment. 21 Of note, 19% of patients developed depression after undergoing concurrent chemoradiation, suggesting a strong interaction of treatment with depression.…”
Section: Discussionmentioning
confidence: 98%
“…Following HNC diagnosis, the prevalence increased to 29.9%. 20 A separate study highlighted that the prevalence of a functional genetic polymorphism of the serotonin transporter gene was not significantly different between control depression patients and HNC depression patients who had completed treatment. 21 Of note, 19% of patients developed depression after undergoing concurrent chemoradiation, suggesting a strong interaction of treatment with depression.…”
Section: Discussionmentioning
confidence: 98%
“…The available literature indicates an increased prevalence of mental disorders among patients with head and neck cancer. In a retrospective analysis of a large insurance claims database, including mental health disorders such as depression, anxiety, nonalcohol drug dependence, adjustment reaction, and depressive disorder not otherwise specified, Lee et al found that patients with a head and neck cancer diagnosis had a prevalence of mental disorders of 29.9% compared with 20.6% before the cancer diagnosis 3 . Moreover, according to a study by Kam et al, there were increased rates of psychological distress and suicide among patients with head and neck cancer compared with the general US population 15 .…”
Section: Discussionmentioning
confidence: 99%
“…An estimated one in five adults experience a mental disorder in the United States (US) each year and it is estimated that almost half of the population in the US will have a mental disorder at some point in their life 1,2 . The prevalence of mental health disorders has been estimated in one study using a national claims database to be even higher (9% increase) in patients with a head and neck cancer diagnosis 3 . Psychiatric comorbidities have additionally been shown to be associated with increased costs and number of hospitalizations for patients with head and neck 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation into mental health insurance claims found that HNC patients had a higher prevalence of mental health diseases at 20.6%, higher than the national estimate at 17.9%. Following HNC diagnosis, the prevalence increased to 29.9% 20 . A separate study highlighted that the prevalence of a functional genetic polymorphism of the serotonin transporter gene was not significantly different between control depression patients and HNC depression patients who had completed treatment 21 .…”
Section: Discussionmentioning
confidence: 99%